Concomitant autoimmune hemolytic anemia and pulmonary embolism associated with mild COVID‐19: A case report - Abdulrahman F. Al‐Mashdali (Wiley, 2021)
Abstract Despite its rarity, AIHA can be associated with COVID‐19. It should be suspected in a patient with recent COVID‐19 presenting with unexplained anemia.